2014
DOI: 10.1590/abd1806-4841.20143004
|View full text |Cite
|
Sign up to set email alerts
|

Application of platelet-rich plasma in the treatment of chronic skin ulcer - Case report

Abstract: The platelet-rich plasma (PRP) has proved promising regarding its applicability in dermatology, especially in the healing of chronic ulcers. The autologous platelet-rich plasma is obtained by centrifuging the blood, so that the components are separated by density gradient. The final product is a gel rich in growth factors that act in tissue repair by activating fibroblasts and inducing extracellular matrix remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 5 publications
0
15
0
4
Order By: Relevance
“…Successful completion of this trial will provide evidence of the best treatment strategy for patients with chronic ulcers. Results from this study can lead to a better understanding of the role of HA as a scaffold and that of the combined technique with PRP as a bio-stimulator in chronic ulcer treatment [2,14]. Overall, the results demonstrated that Group 2 (PRP + HA) represents a positive system for injured cells and tissue regeneration.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Successful completion of this trial will provide evidence of the best treatment strategy for patients with chronic ulcers. Results from this study can lead to a better understanding of the role of HA as a scaffold and that of the combined technique with PRP as a bio-stimulator in chronic ulcer treatment [2,14]. Overall, the results demonstrated that Group 2 (PRP + HA) represents a positive system for injured cells and tissue regeneration.…”
Section: Discussionmentioning
confidence: 84%
“…A correct approach is fundamental [1]. The Wound Bed Preparation guideline advises that after diagnosis the expert should correct the biological state of the ulcer micro-environment [2] based on TIME principles (Tissue, Infection, Moisture balance, Epidermal) [3]. The most important issue is to change the two discriminant factors: super-infection and exudation.…”
Section: Introductionmentioning
confidence: 99%
“…PRP has a wide range of application in wound healing, cartilage, bone, musculoskeletal regeneration, oral surgery, dentistry, and cosmetics [8,9,10,11,12,13]. Moreover, PRP has been successfully applied in treating endometriosis, chronic skin ulcer and vitiligo in earlier studies [14,15]. Nevertheless, there are some drawbacks of using PRP [16].…”
Section: Introductionmentioning
confidence: 99%
“…PRP is a product derived from the centrifugation of whole blood that is rich in structural proteins and is used to promote the production of large amounts of growth factors, which stimulate collagen and extracellular matrix production with minimal amounts of plasma, which is an important alternative in cases where conventional treatments are not successful …”
Section: Introductionmentioning
confidence: 99%